Towards the enrichment of Construction VET courses for the Green and Digital Transition: The Buildskills Academy Paradigm - Yiatros, Stylianos; Vryonidi, Sara Mariza; Konstantinou, Eirini; Christou, Antonia; Tantele, Elia; Savva, Georgia C.; Peynovski, Lyubomir; Hamanova, Mariyana; Nakova, Maria (My University, 2025)
As the construction sector faces digital and green transitions, vocational education and training (VET) systems have struggled to keep pace. The BuildSkills Academy addresses this gap through a Europe-wide network focused on upskilling and reskilling of the construction workforce with certified transitional competencies. Central to this effort is the BuildEnrichedSkills Methodology (BESM), a structured framework that enhances VET courses across EQF levels 3-7 with green and digital skills. BESM involves a self-assessment tool, gap analysis for 38 construction professions and tailored course enrichment. Key gaps identified include limited training in life cycle assessment, nature-based systems, and digital risk modelling. This article presents two EQF level 6 pilot courses enriched through BESM, to be piloted by the Cyprus University of Technology. The first, Bio-inspired Innovation and Design for Sustainable Engineering, uses biomimicry and tools like the Copernicus Climate Atlas to teach climate-responsive design. The second, Risk and Reliability in Health and Safety, builds learners’ capacity to assess structural uncertainty and human error through risk analysis techniques. These pilots show how BESM can equip learners with future-ready skills and support systemic change in construction education.
Keywords: Construction; VET; digital transition; green transition